Authorship and appropriation in artificial intelligence generated artworks - Karakaidou, Sofia (2019)
The rapid development of cognitive sciences in the context of Artificial Intelligence (AI) and its supersonic immersion into almost every field, including that of the arts, urges culture studies to closely review the authorship and framework of such artworks. Supported by the popular culture representations in science-fiction films and prolific media headlines that aim to capture our attention among the multitude of information available, AI slips through as an abstract idea. Data, as the sine qua non of Artificial Intelligence, require us to look into the structure of technological methods used to produce art and examine the subtle influence of the human factor behind big digital data. Attempting to escape the non-humanization of the provenance of AI, we will examine the author’s intention and potential gender or racial discrimination pitfalls. Moreover, by reviewing the historical evolution of machine-made art as well as some recent examples of corporate cultural patronage initiatives, this research aims to examine the conditions that frame the existence and further development of art made with code. Overall, this dissertation aims to investigate how AI is used in art production and examine whether or not AI impacts on the authorship of an artwork, and what the nature of that impact is.